Evaluasi dan Optimasi Kinerja MySQL Master-Slave dengan Metode Kuantitatif pada Database Pemohon Tes Psikologi SIM PT XYZ pada POLDA METRO JAYA - Haryoto, Iin Sahuri; Firmansyah, Gerry; Tjahjono, Budi; Widodo, Agung Mulyo; Akbar, Habibullah; Fatonah, Nenden Siti (Riviera Publishing, 2025)
The development of information technology and cloud computing has enabled organizations to manage large-scale data efficiently. PT XYZ, which is engaged in psychological testing for Driving Licenses (SIM), uses a web-based system with a MySQL database that has implemented master-slave replication. However, as the data volume increases to 4,000-5,000 entries per day, the system experiences performance constraints, especially in the speed of read and write queries. This study aims to optimize the performance of the MySQL database by adjusting the server configuration and specifications to improve system efficiency. The test results show that server specification settings, including processor speed, memory size, and replication configuration, play an important role in improving system performance. By adjusting the master and slave server configurations, the system shows a significant increase in database response time and operational efficiency. This optimization is expected to be a reference in the implementation and management of large-scale databases using MySQL replication.